A hand not shortened - Jeynes, William (Emerald Publishing Limited : Information Age Pub., 2005)
A Hand Not Shortened is a comprehensive theological book on the creative workings of the grace of God in ten of the great individuals of the Bible. Very few books examine exegetically the dynamics of the grace of God in such detail. The primary theme of the book is that God adjusts the workings of His grace to each of these great individuals' situations. Theologically speaking, God's grace is not restricted to parameters that apply only to pristine individuals or to those who were raised in privileged circumstances. Rather, God's grace is characterized by great flexibility to reach any individual in a variety of circumstances. This fact has grand theological and practical implications. It gives hope to the theologian whose primary declaration is that 'God is Love' and stirs the aspirations of the seeker who longs to hear that God really cares. This book focuses of the lives of many great individuals from the Bible including Abraham, Jacob, Joseph, Moses, David, Peter, Paul, and others as well. This book will have a deep impact upon both the theologian and the seeker.